Finland - Lee, Tan Chung (Milwaukee, Wisconsin : Gareth Stevens, 1998)
Describes how the culture of Finland is reflected in the celebration of festivals throughout the year, including Midsummer Festival, Pikkujoulu, Shrove Tuesday, and Students' Day.